Comparative Analysis of Thermodynamic Characteristics of Permanent Magnet and Electromagnetic Eddy Current Braking - Yapeng HAN; Min ZHANG; Weihua MA; Shihui LUO (机车电传动)
Electromagnetic eddy current braking devices often used in high-speed trains due to the advantages of not being limited by train adhesion and low attenuation. However, its large size and mass, and high temperature rise of magnetic poles, prevent it from further application. In this paper, a permanent magnet eddy current braking scheme was proposed based on the electromagnetic eddy current braking device. Based on theoretical calculations and simulation analysis, the air-gap magnetic fields of two eddy-current braking devices with the same pole distance and structure size were compared, and the relationship between eddy-current braking force and air-gap magnetic field was obtained. Braking force and attractive force of permanent magnet and electromagnetic eddy current braking devices under the same structure size were calculated and the changes of average temperature of magnetic poles of two devices with speed were compared. The results show that the braking force calculation methods of permanent magnet and electromagnetic eddy current braking are equivalent. The braking force of permanent magnet eddy current braking force under the same structure can reach 3.29 times of the electromagnetic eddy current braking with standard excitation parameters. When the braking force is the same, the temperature rise of the magnetic pole of the permanent magnet eddy current brake is smaller.